2020
DOI: 10.1007/s10689-020-00171-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported burden of intensified surveillance and surgery in high-risk individuals under pancreatic cancer surveillance

Abstract: In high-risk individuals participating in a pancreatic cancer surveillance program, worrisome features warrant for intensified surveillance or, occasionally, surgery. Our objectives were to determine the patient-reported burden of intensified surveillance and/or surgery, and to assess post-operative quality of life and opinion of surgery. Participants in our pancreatic cancer surveillance program completed questionnaires including the Cancer Worry Scale (CWS) and the Hospital Anxiety and Depression Scale (HADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
7
1
3
Order By: Relevance
“…In another Italian study comparing surgically treated IPMN patients to IPMN patients undergoing follow-up, patients being followed felt less healthy and experienced more anxiety and stress than surgical patients [ 9 ]. This result differed from a Dutch study [ 10 ], which found that high-risk individuals under pancreatic cancer surveillance only temporarily exhibited increased cancer worries and, in the long term, surveillance reduced their concern and provided a sense of certainty. Their study was conducted on patients at a higher risk for pancreatic cancer, however, not on IPMN patients.…”
Section: Introductioncontrasting
confidence: 99%
“…In another Italian study comparing surgically treated IPMN patients to IPMN patients undergoing follow-up, patients being followed felt less healthy and experienced more anxiety and stress than surgical patients [ 9 ]. This result differed from a Dutch study [ 10 ], which found that high-risk individuals under pancreatic cancer surveillance only temporarily exhibited increased cancer worries and, in the long term, surveillance reduced their concern and provided a sense of certainty. Their study was conducted on patients at a higher risk for pancreatic cancer, however, not on IPMN patients.…”
Section: Introductioncontrasting
confidence: 99%
“…Thus, false positive outcomes are common, as our results show. Also, we established that this often leads to an intensified follow‐up regimen, which could cause harm due to unnecessary diagnostic procedures (such as EUS/FNA) and psychological distress 17–19 . Moreover, in the current study, 45% of operated individuals underwent surgery for benign disease, while we know that pancreatic surgery is associated with substantial grade III‐IV (Clavien‐Dindo) morbidity (4%–31%) and mortality (2%–6%) 20–24 …”
Section: Discussionmentioning
confidence: 66%
“…Finally, we have yet to be able to analyze data at a patient level, and we have not been able to evaluate and quantify the perception of HRIs under surveillance toward surgery, balancing the weight of undergoing a possibly unnecessary physical harm (the greatest being for total pancreatectomy, that impact adversely and somehow irreversibly the quality of life, 55 in this series occurring in 13.7% of cases), with the psychological burden of the repeated examinations of the follow-up for a preneoplastic lesion, already reported for HRI undergoing pancreatic cancer surveillance. 56 In conclusion, surgical resection of low-yield lesions not considered CAPS guidelines goals may occur in a small subset of HRIs undergoing pancreatic cancer surveillance. Such lesions may be deemed to have been resected before they turn into cancer, eventually reducing risks, but they may also have never become malignant.…”
Section: Discussionmentioning
confidence: 92%
“…Also, despite extensive efforts to avoid duplication, we cannot exclude that CAPS-based studies may partially include overlapping populations. Finally, we have yet to be able to analyze data at a patient level, and we have not been able to evaluate and quantify the perception of HRIs under surveillance toward surgery, balancing the weight of undergoing a possibly unnecessary physical harm (the greatest being for total pancreatectomy, that impact adversely and somehow irreversibly the quality of life, 55 in this series occurring in 13.7% of cases), with the psychological burden of the repeated examinations of the follow-up for a preneoplastic lesion, already reported for HRI undergoing pancreatic cancer surveillance 56 …”
Section: Discussionmentioning
confidence: 95%